PENGEMBANGAN PANDUAN PRAKTIKUM PERANGKAT GELOMBANG MIKRO PADA MATERI GELOMBANG ELEKTROMAGNETIK DI PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNSRI - Septri Rahayu (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
This research has successfully developed practical guide microwave valid devices and therefore can be used in practical lab activities, especially on the subject matter of electromagnetic waves in a wave of Physical Education Laboratory using a microwave device. This type of research is research development by using a model consisting of Plomp initial investigation phase, design phase, the realization phase, test phase, evaluation and revision. Practical guide arranged according to the criteria developed lab manual that consists of a title practicum, practicum objectives, the basic theory, tools and materials, working step, the observed data, analysis, and conclusions. Practical guide developed is a reflection (reflection) waves, diffraction and polarization gap that can be used on subjects waves. Data collected through expert validation, student response sheet questionnaires, and interviews. The results of the third assessment validator, otherwise very valid practical guide with a score of 4.53 (scale range 1-5), while the results of the questionnaire responses of the three groups of students expressed a practical guide practicum 80.61%. The weakness in this study is the limited availability of microwave devices so that the user testing stage is only carried out on 3 groups with different times. This practical guide can be used in physical education students perform lab activities using the microwave in the Laboratory of Physical Education FKIP UNSRI.